Effect of LF Soft Bubbling Time on Inclusions in Tire Cord Steel LX82 A - Zhao Haoqian, Zhang Yuming, Ma Bo, Gong Yanjie, Meng Yaoqing (Teshugang)
For the control of cord steel inclusion， long time soft bubbling treatment is usually chosen to improve the cleanliness of molten steel， but it will lead to the increased erosion of magnesia-carbon bricks. Through the industrial production test， the effects of soft blowing time after LF refining on the composition and quantity of oxide inclusions of cord steel wire rod were studied by means of FEI Explorer 4 automatic scanning electron microscopy. Becca standard score and Kobe Standard Max-T （ave） score were used to evaluate the inclusion of wire rod. The results showed that the composition of oxide inclusions larger than 3 μm in the wire rod was similar to that in the process of soft blowing time of 45 min and 25 min after LF refining， and the density of inclusions was 135 /100 mm2 and 103 /100 mm2， respectively. The density of inclusions in the process of soft blowing time of 25 min after LF refining was slightly lower. Expanding the number of comparison tests， the score of Kobe standard Max-T （ave） and Becca standard indicate that the inclusions control of soft bubbling process for 20-25 min did not become worse or slightly improved. The control of low melting point inclusions in cord steel was mainly through controlling Al content， refining slag and other process parameters， and the inclusions that lead to the failure of the final product are often inconsistent with the types of endogenous inclusions. For cord steel， it can be considered to reduce the soft blowing time after LF refining.